2023
DOI: 10.1111/luts.12495
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in the postpartum 1‐year period: Its prevalence and effect on psychosocial status of women

Abstract: ObjectivesIn this study, it was aimed to determine the prevalence and effect of urinary incontinence in the postpartum 1 year period on psychosocial status of women.MethodsThis study with a cross‐sectional and descriptive design was conducted between 01.10.2021 and 01.04.2022. There were 406 women in the postpartum 8 weeks to 1 year period who participated in the study. The data were collected through Identifying Information Form, Edinburgh Postnatal Depression Scale, and Nottingham Health Profile.ResultsIn th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Chronic ischemia can affect the long-term health of pelvic organs and contribute to pelvic floor dysfunction. Studies have shown that urinary incontinence is common during pregnancy and the postpartum period, with a prevalence of incontinence seen in about one-fifth of women within the first year after childbirth [ 29 - 30 ]. Our study found that six months after childbirth, the rates of SUI were 17.7% and UUI were 5.2%, which is consistent with the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ischemia can affect the long-term health of pelvic organs and contribute to pelvic floor dysfunction. Studies have shown that urinary incontinence is common during pregnancy and the postpartum period, with a prevalence of incontinence seen in about one-fifth of women within the first year after childbirth [ 29 - 30 ]. Our study found that six months after childbirth, the rates of SUI were 17.7% and UUI were 5.2%, which is consistent with the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that individuals often experience psychological distress, such as anxiety, embarrassment and impaired self-esteem, when dealing with UI issues. 36,37 These psychological factors can have an impact on their perception and expression of needs related to psychological comfort and social participation.…”
Section: Discussionmentioning
confidence: 99%
“…Parturition stands as a critical life event for women, and urinary incontinence profoundly compromises their psychophysical well-being and quality of life. Various studies have demonstrated that urinary incontinence augments the risk of postpartum depression [ 4 6 ]. Consequently, heightened vigilance towards the incidence of postpartum incontinence in women is imperative.…”
Section: Introductionmentioning
confidence: 99%